Vigabatrin-Associated Visual Field Defects - J Gordon Millichap (Pediatric Neurology Briefs)
The prevalence, risk factors, and long-term outcome of vigabatrin-associated visual field defects were examined in 60 adult patients with partial epilepsy treated with vigabatrin for 7 months to 14 years at the University of Kuopio Hospital, Finland.